(untitled) (Slavic Studies, 2024)
The paper is evaluating the Macedonian phraseological equivalents of Slovenian phrasemes in the Dictionary of Slovenian Phrasemes by Janez Keber (2011, 2015). Possible sources for the excerption of Macedonian phraseological material are presented, the cross-linguistic phraseological equivalence of the given units at the semantic, constituent and representational levels is checked, as well as the observed shortcomings or errors in citing Macedonian equivalents. In case of detected errors, suggestions are also given for a more appropriate display or corrections of Macedonian phraseological equivalents.